Effect of withdrawal of co-proxamol on prescribing and deaths from drug poisoning in England and Wales: time series analysis. (18th June 2009) - Hawton, Keith; Bergen, Helen; Simkin, Sue; Brock, Anita; Griffiths, Clare; Romeri, Ester; Smith, Karen L; Kapur, Navneet; Gunnell, David
Abstract : Objective To assess the effect of the UK Committee on Safety of Medicines' announcement in January 2005 of withdrawal of co-proxamol on analgesic prescribing and poisoning mortality. Design Interrupted time series analysis for 1998-2007. Setting England and Wales. Data sources Prescribing data from the prescription statistics department of the Information Centre for Health and Social Care (England) and the Prescribing Services Unit, Health Solutions Wales (Wales). Mortality data from the Office for National Statistics. Main outcome measures Prescriptions. Deaths from drug poisoning (suicides, open verdicts, accidental poisonings) involving single analgesics. Results A steep reduction in prescribing of co-proxamol occurred in the post-intervention period 2005-7, such that number of prescriptions fell by an average of 859 (95% confidence interval 653 to 1065) thousand per quarter, equating to an overall decrease of about 59%. Prescribing of some other analgesics (co-codamol, paracetamol, co-dydramol, and codeine) increased significantly during this time. These changes were associated with a major reduction in deaths involving co-proxamol compared with the expected number of deaths (an estimated 295 fewer suicides and 349 fewer deaths including accidental poisonings), but no statistical evidence for an increase in deaths involving either other analgesics or other drugs. Conclusions Major changes in prescribing after the announcement of the withdrawal of co-proxamol have had a marked beneficial effect on poisoning mortality involving this drug, with little evidence of substitution of suicide method related to increased prescribing of other analgesics.